Extension and Grassroots Educators’ Approaches to Participatory Education: Interrelationships among Training, Worldview, and Institutional Support - Nancy Grudens-Schuck (Adult Education Research Conference, 2000)
This paper focuses on development of adult educators' commitment to participatory education through the presentation of empirical results from a study of a Canadian sustainable agriculture program. The author argues for an account of professional development that integrates institutional and historical dimensions.